Delayed Union in Pediatric Bennett’s Fracture Treated with Open Reduction and Internal Fixation Using Kirschner Wire: A Case Report - Aga Shahri Putera Ketaren; Gusnur Gazali Ashari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Bennett’s fracture is a fracture-subluxation of the thumb carpometacarpal joint, occasionally seen in pediatric patients. Despite the frequency of metacarpal fractures, limited data exist on outcomes and complications in children. Optimal surgical treatment remains unclear. This case report aims to describe a rare instance of delayed union in a pediatric Bennett’s fracture treated with Kirschner wire fixation and to contribute to the limited evidence guiding its management. This is a descriptive case report. Data were collected through clinical examination, surgical records, and serial imaging, and were analyzed descriptively to assess healing progression and function. A 14-year-old boy presented three weeks post-injury with persistent thumb pain after a karate trauma. Imaging confirmed a Bennett’s fracture. He underwent open reduction and internal fixation (ORIF) using Kirschner wires. Although initial recovery was uneventful, delayed union was noted at three months, requiring prolonged observation. Complete union occurred at five months, with good functional outcome. Delayed union can occur in pediatric Bennett’s fractures, even with stable fixation. This report emphasizes the need for accurate reduction, extended monitoring, and further documentation to inform pediatric surgical protocols.